2017
DOI: 10.1136/bjophthalmol-2017-310510
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of intracameral mydriasis for routine cataract surgery

Abstract: Intracameral mydriasis was clinically effective in most patients undergoing cataract surgery and might be associated with an improved patient experience and a more streamlined preoperative flow. Mydrane represents a licensed alternative to the off-label use of other intracameral mydriatic agents, but was not judged to be a cost-effective intervention for routine use in this particular setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
(13 reference statements)
2
13
1
Order By: Relevance
“…An increased emphasis has been placed on using local anesthesia and administering drugs intracamerally, and studies have shown that intracameral drug administration induces rapid and safe mydriasis. 2,7,8 Studies have focused not only on pupil dilators but also on anti-inflammatory agents and means of maintaining mydriasis with medications injected intracamerally. 16 The introduction and registration of the first ready-to-use combined mydriatic and anesthetic, which can be intracamerally injected, have provided surgeons with a new tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased emphasis has been placed on using local anesthesia and administering drugs intracamerally, and studies have shown that intracameral drug administration induces rapid and safe mydriasis. 2,7,8 Studies have focused not only on pupil dilators but also on anti-inflammatory agents and means of maintaining mydriasis with medications injected intracamerally. 16 The introduction and registration of the first ready-to-use combined mydriatic and anesthetic, which can be intracamerally injected, have provided surgeons with a new tool.…”
Section: Discussionmentioning
confidence: 99%
“…A new study from a single center assessed pupil diameter during surgery and visual acuity postoperatively; however, this study utilized different measurement points and assessed outcomes based on patient feedback rather than surgeon feedback. 8…”
Section: Introductionmentioning
confidence: 99%
“…According to our results, the study drug Mydrane™ and the traditional anesthetic formulation seems to have similar efficacy in attenuating pain. Other studies indicated Mydrane™ to be effective also as an intraoperative mydriatic (Labetoulle et al, 2016;Schulz et al, 2018). For these considerations, Davey et al shown that Mydrane™ is a cost effective and safe procedure in United Kingdom (Davey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a third strategy consisting of an intracameral injection of tropicamide, phenylephrine, and xylocaine (Mydrane ® ) was brought to the market. This product is only indicated for pre-surgery mydriasis because of the presence of an anesthetic in its composition and its administration route [11,12].…”
Section: Introductionmentioning
confidence: 99%